EPISTEME AND HUMAN SEMOVENCE: THE SCIENTIFIC KNOWLEDGE IN JEAN PIAGET AND AND ANTROPOLOGYOF KINETICS (Fiep Bulletin - online, 2012)
The Swiss biologist Jean Piaget seems to be the last erudite scientist of all times. Substantialphilosophical education underlies his unusual multi interscientific wisdom; therefore Piaget reached the top asone of the best theorists of science in contemporary times. His “Genetic Epistemology” will continue to riseinterest worldwide. By linking the validity of knowledge to the model of its construction, Piaget underlines themediating role of human self moving, which he names “motricité”. By extension, Piaget also highlights itsanthropogenic function, and this is precisely the main nexus between Piaget's theory of science and theboundaries of human self moving study. Gymnastics in ancient times, Physical Education in late modernsocieties, and currently referred to as a number of disciplinary meanings (sometimes confusing or paraphrasing),this discipline shows that its prior vocation is anthropological: all the scientific and philosophic pluralism ofknowledge is firstly related to man as a self-moving subject.This paper labels that special discipline as “Kinanthropology”, but will not discusse possible similaritiesto “Science of Human Kinetics” (Sergio, 1987) or to “Sichbewegen”, the anthropological version from “FrankfurterArbeitsgruppe” and other pedagogues (Kunz, 2006; Trebels, 1989) in the German sport science: it is all about thequestion on disciplinary knowledge, whose object is human self moving, named as “noetic parentage” by Piaget.This parentage searching for the human self moving discipline corresponds to the various types of knowledgewith regard to the science system. According to Piaget, that system denotes a horizontal structure of circularnature and succeeding stamp, where the variety of disciplines gathers in groups via parentage links between theirrespective objects of study and theory. For this reason, science classification is similar to the search for the “noeticparentage” of disciplines and their mutual dependencies. On that account, Piaget disposes four groups ofsciences: logical-mathematical, physical, biological, and psycho-sociological. On the other hand, each disciplinearranges its own information in four domains: one related to the objects of study, other on the objects' theories, thethird on disciplinary fundamentals (proper explanation, methodology), and the fourth on subject-objectdependency (what helps to search how knowledge is possible). As reported above, human self moving, taken asa specific discipline, will be concurrently biological and psycho-sociological since its objects and theories are allrelated to man: a complex “being” at the same time physical, organic, self-conscious, social, and cultural. Henceefforts to justify an epistemological hypothesis about it shall emerge and thus Kinanthropology (as labelledbefore) might likely be considered an interscience rather than a discipline.